2023
DOI: 10.7150/ijms.80684
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 deficiency inhibits proliferation and invasion of trophoblasts via the SFRP2/Wnt/β-catenin pathway in fetal growth restriction

Abstract: Background: Fetal growth restriction (FGR) is characterized by restricted fetal growth and dysregulated placental development. The etiology and pathogenesis still remain elusive. IL-27 shows multiple roles in regulating various biological processes, however, how IL-27 involves in placentation in FGR pregnancy hasn't been demonstrated. Methods: The levels of IL-27 and IL-27RA in FGR and normal placentae were determined by immunohistochemistry, western blot and RT-PCR. HTR-8/SVneo cells and Il27ra -/-murine mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…While Jahantigh found a positive correlation between elevated IL‐27 levels and PE severity, 9 Yin's research showed no notable contrast in serum IL‐27 levels between the control and PE groups but noticed a surge in the expression of IL‐27 and its receptors in trophoblast cells in PE. 36 Additionally, Zhang found that IL‐27 can encourage the proliferation, migration, and invasion of trophoblast cells, 37 while Ge found that IL‐27 regulates the epithelial‐mesenchymal transition of trophoblast cells, thereby inhibiting their migratory and invasive capacity, and contributing to the pathogenesis of PE. 38 These discrepancies could be due to differences in sample size, time of onset of PE, and IL‐27 concentrations applied in in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…While Jahantigh found a positive correlation between elevated IL‐27 levels and PE severity, 9 Yin's research showed no notable contrast in serum IL‐27 levels between the control and PE groups but noticed a surge in the expression of IL‐27 and its receptors in trophoblast cells in PE. 36 Additionally, Zhang found that IL‐27 can encourage the proliferation, migration, and invasion of trophoblast cells, 37 while Ge found that IL‐27 regulates the epithelial‐mesenchymal transition of trophoblast cells, thereby inhibiting their migratory and invasive capacity, and contributing to the pathogenesis of PE. 38 These discrepancies could be due to differences in sample size, time of onset of PE, and IL‐27 concentrations applied in in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Next, fresh complete medium was substituted for further cultivation. The infection efficiency was evaluated by Western blot 48 h after infection [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The PVDF membranes were incubated with primary antibodies against CYP27B1 (1:500, ab206655, abcam), β-catenin (1:500, Abcam, ab230169) or GAPDH (1:1000, ab75479, abcam) overnight at 4 °C respectively. Then PVDF membranes were washed with PBST solution three times and treated with peroxidase-conjugated goat anti-rabbit IgG secondary antibody (1:5000; Bioworld Technology, BS10003) or goat anti-mouse IgG secondary antibody (1:5000; Bioworld Technology, BS10003) at room temperature for 1 h. After adequate washing, Immobilon Western Chemiluminescent HRP Substrate Kit (Millipore, WBKLS0100) was used for chemiluminescence detection [ 16 ].…”
Section: Methodsmentioning
confidence: 99%